A 2D Blade Element Study of a Wind Turbine Rotor under Yaw Loads. Issue 5 (October 2015) - Gharali, Kobra; Johnson, David A.; Lam, Vivian; Gu, Mingyao
Wind turbines operate within an environment of varying wind direction and magnitude leading to misalignment or yaw between the wind and the turbine rotor. Many control techniques have been applied to small horizontal axis wind turbines (HAWTs) to prevent significant yaw loads, but in reality, most of the time the rotor is under some yaw load which may be significant. A blade element of a HAWT rotor under yaw loading is similar to a sinusoidally pitching airfoil. Here a miniaturized pitching S822 airfoil with a reduced frequency k of 0.025 at a Reynolds number ( Re = 10 5 ) is considered where the maximum dynamic angle of attack is equal to the static angle where the maximum lift to drag ratio occurs. These dynamic results obtained with laser Doppler anemometry (LDA), particle image velocimetry (PIV) and a numerical simulation with the Transition SST method are compared to a constant wind-loaded blade element. Since direct load measurement for dynamic miniaturized models in wind tunnels is very challenging, the non-intrusive PIV control volume analysis approach has been applied for load determination. Unlike the rotor in an ideal unidirectional freestream flow, a rotor under yaw loads, as presented here, experiences significant unbalanced loading in one cycle and a non-uniform wake. Results may be used to predict the cyclical range of loads a blade element experiences in yaw conditions and effects on the downstream rotor wake.